2021
DOI: 10.1080/10717544.2021.1958106
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, characterization, and cellular toxicity assessment of tamoxifen-loaded silk fibroin nanoparticles in breast cancer

Abstract: Silk fibroin (SF) is a natural polymeric biomaterial that is widely adopted for the preparation of drug delivery systems. Herein, we aimed to fabricate and characterize SF nanoparticles loaded with the selective estrogen receptor modulator; tamoxifen citrate (TC-SF-NPs) and to assess their in vitro efficacy against breast cancer cell lines (MCF-7 and MDA-MB-231). TC-loaded SF-NPs were characterized for particle size, morphology, entrapment efficiency, and release profile. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…Recent advances in nanotechnology provide new opportunities for the development of innovative delivery vehicles based on unique types of nanoparticulate systems with varying sizes and shapes and malleable antibacterial activities. One of the most appealing features of nanoparticle-based formulations is their capacity to deliver a wide arsenal of drugs, either attached to their surfaces or entrapped within their core structure, to the site of infection efficiently and safely [14][15][16]. By enhancing the pharmacokinetic behavior and, thereby, pharmacological activity of entrapped/loaded drug entities, compared to free drug counterparts, the administered dose needed to produce the designated therapeutic effect can be reduced considerably [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in nanotechnology provide new opportunities for the development of innovative delivery vehicles based on unique types of nanoparticulate systems with varying sizes and shapes and malleable antibacterial activities. One of the most appealing features of nanoparticle-based formulations is their capacity to deliver a wide arsenal of drugs, either attached to their surfaces or entrapped within their core structure, to the site of infection efficiently and safely [14][15][16]. By enhancing the pharmacokinetic behavior and, thereby, pharmacological activity of entrapped/loaded drug entities, compared to free drug counterparts, the administered dose needed to produce the designated therapeutic effect can be reduced considerably [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors investigated the reactive oxygen species levels after treating the cell lines with the developed biomaterials and observed that the reactive oxygen species levels were lower in two cell lines, namely MCF-7 and HFF. These findings highlight the great contribution of SF-based biomaterials in cancer therapy [ 183 ].…”
Section: Sf In Cancer Therapymentioning
confidence: 89%
“…Furthermore, the therapeutic activity resulting from this formulation was higher than other approaches [ 182 ]. In the same year, Moin et al (2021) [ 183 ] developed both nano- and micro-fibroin-based particles as drug delivery systems to encapsulate doxorubicin. The authors used two types of cancer cell lines, specifically MCF-7 and SAOS2, and one normal human cell line, namely HFF.…”
Section: Sf In Cancer Therapymentioning
confidence: 99%
“…Furanodienone (FDN) is an emerging bioactive furanosesquiterpenoid with diverse pharmacological activities, such as anti-inflammatory and antimicrobial activities [6]. Recently, many reports have emphasized its cytotoxic potential against different cancer cell lines, including colorectal cancer and breast cancer [7,9,21]. However, the antiproliferative potential of FDN against human lung cancer has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of furanodienone (FDN) on A549 cells was initially evaluated at varying concentrations, ranging from 0 to 300 µM, to determine the appropriate FDN concentration(s) to be used throughout the study using the standard procedure of MTT as previously described [9]. From this study, FDN concentrations of 50, 100, and 200 µM, which exerted remarkable cytotoxic potential, were selected to be used throughout the whole study.…”
Section: Cytotoxicity Estimationmentioning
confidence: 99%